Capillary crystallization type waterproof agent as well as preparation method and application thereof

By using a toughening agent mixed with end carboxylic liquid rubber modified epoxy resin and inorganic ceramic particles in concrete, combined with alkylphenol polyoxyethylene ether as a dispersant, the existing permeable crystalline waterproofing agent has been solved, resulting in the decline of the mechanical properties of concrete due to the existing penetration of crystalline waterproofing agent. The problem of this has achieved efficient anti-seepage and bending performance improvement.

CN119461943APending Publication Date: 2025-02-18BEIJING MUHU CONCRETE ADMIXTURE CO LTD

Patent Information

Application Number
CN202411640039.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

While the existing permeable crystalline waterproofing agents improve the permeability of concrete, they will lead to a decrease in the mechanical properties of concrete, especially the bending resistance.

Method used

A toughening agent is made by mixing end carboxylic liquid rubber modified epoxy resin and inorganic ceramic particles at a mass ratio of 7:3-5, combined with alkylphenol polyoxyethylene ether as a dispersant, and is evenly dispersed in the concrete, thereby Improve the overall toughness of concrete.

Benefits of technology

It significantly improves the permeability and bending properties of concrete, can resist cracking at the source, reduce cracks and pores, prevent moisture infiltration, and improve the bending properties of concrete after water permeability and rehealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138190230000051
    Figure BDA0005138190230000051
Patent Text Reader

Abstract

The invention provides a capillary crystalline waterproof agent, a preparation method and application, and the capillary crystalline waterproof agent comprises the following raw materials in parts by weight: 80-100 parts of a non-cement-based cementing material, 15-25 parts of an alkali activator, 1.5-2.5 parts of a thickener, 12.5-22.5 parts of a flexibilizer, 0.1-0.3 part of a dispersant and 5-10 parts of a water reducer, the flexibilizer is formed by mixing carboxyl-terminated liquid rubber modified epoxy resin and inorganic ceramic particles according to the mass ratio of 7: (3-5), and the dispersing agent is alkylphenol polyoxyethylene ether. Under the action of the dispersing agent, the toughening agent can be uniformly dispersed in the concrete, so that the overall toughness of the concrete is improved. The improvement of the overall toughness not only can bear deformation or shrinkage cracking of the concrete caused by evaporation of moisture, temperature difference and external stress, but also can better resist cracking from the source, reduce cracks and pores, prevent moisture from permeating and improve the impermeability of the concrete; and the bending resistance of the concrete after complete water permeability and self-healing can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of penetrating crystalline waterproofing agents, and specifically relates to a penetrating crystalline waterproofing agent, a preparation method and an application thereof. Background Art

[0002] Concrete is a mixture of water, cement, coarse aggregate and fine aggregate. Differences in raw materials, construction technology and design can lead to leakage. Leakage often originates from cracking. The reasons for cracking include: concrete mix ratio, structural design and curing age; a large amount of free water evaporates in the early stage of hydration, and the temperature difference between the inside and outside is too large, resulting in uneven stress, which leads to deformation or shrinkage cracking. When the tensile stress on the surface of the structure is less than the tensile stress, microcracks will appear in the concrete, and as water enters, the microcracks will expand into cracks.

[0003] When concrete leaks, harmful substances will enter the concrete through cracks, fissures and pores, leading to corrosion of steel bars, thus endangering the structural safety of the building. Waterproofing agent is an admixture used to reduce the water permeability of concrete under hydrostatic pressure. It is used to prepare waterproof concrete, which can reduce water seepage and water absorption of concrete and enhance its waterproof or hydrophobic properties.

[0004] Penetrating crystallization waterproofing agent is a mixture of organic and inorganic chemicals. Under the action of water, it enters the internal pores of concrete through the seepage channel or the normal capillary action of concrete, and reacts with the unhydrated cement particles in the concrete to form film-forming hydrated crystals, which block the pores, capillaries and cracks of the concrete, thereby achieving the purpose of waterproofing. Penetrating crystallization waterproofing agent has good compatibility with the concrete matrix, not only has good anti-seepage ability, but also has a certain self-repairing ability, can significantly improve the service life of concrete, and is currently one of the most commonly used waterproofing agents for controlling concrete cracks and pore size. For example, a penetrating crystallization waterproofing agent disclosed in patent CN102432222B is mixed in proportion (mass percentage): ultrafine mineral powder: 35%-65%, fly ash: 15%-30%, calcium hydroxide: 8%-20%, nano silicon dioxide: 1%-3%, silicone additive: 5%-14%, sodium polyacrylate: 0%-2.4%, polycarboxylic acid water reducer: 0.1%-1.5%. Patent CN102060460B discloses an inorganic cement penetrating crystalline waterproofing agent and a production process thereof. The material is composed of silica fume, sodium silicate, bentonite, fly ash, polypropylene fiber and sulfonate water reducer in a certain percentage ratio.

[0005] The above-mentioned penetrating crystallization waterproofing agent is prepared with ultrafine mineral powder, fly ash, silica fume and other cementitious materials as the main active ingredients. It not only obtains a waterproofing agent with good impermeability, good self-healing performance and strong bonding force, but also comprehensively recycles solid waste. Due to the reaction between the waterproofing agent and the components in the cement, the type and distribution of the hydration products and the microstructure of the concrete change. Although the internal pores and microcracks are filled to prevent the penetration of water, the expansion and distribution of the microcracks under load are restricted and changed, and the overall toughness of the concrete decreases, that is, the bending resistance decreases.

[0006] Therefore, it is necessary to develop a penetrating crystalline waterproofing agent which has excellent anti-seepage performance and no adverse effect on the mechanical properties of concrete. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a penetrating crystallization waterproofing agent, which is a toughening agent mixed with a carboxyl-terminated liquid rubber modified epoxy resin and inorganic ceramic particles in a mass ratio of 7:3-5. Under the action of the dispersant alkylphenol polyoxyethylene ether, the toughening agent can be evenly dispersed in the concrete, thereby improving the overall toughness of the concrete. This improvement in overall toughness can not only withstand the deformation or shrinkage cracking caused by the evaporation of water, temperature difference, and external stress of the concrete, but also better resist cracking at the source, reduce cracks and pores, prevent water from penetrating, and improve the anti-seepage performance of the concrete; it can also improve the bending resistance of the concrete after it is fully permeable and self-healed.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A penetrating crystalline waterproofing agent comprises the following raw materials in parts by weight: 80-100 parts of non-cement-based cementitious materials, 15-25 parts of alkali activators, 1.5-2.5 parts of thickeners, 12.5-22.5 parts of toughening agents, 0.1-0.3 parts of dispersants, and 5-10 parts of water reducers. The toughening agent is prepared by mixing carboxyl-terminated liquid rubber-modified epoxy resin and inorganic ceramic particles in a mass ratio of 7:3-5, and the dispersant is alkylphenol polyoxyethylene ether.

[0010] The carboxyl-terminated liquid rubber modified epoxy resin is an adduct of carboxyl-terminated liquid rubber and epoxy resin, and has an epoxy equivalent of 1200-1800 g / eq.

[0011] Compared with inorganic ceramic particles, the surface of carboxyl-terminated liquid rubber-modified epoxy resin has polar epoxy groups. The surface of inorganic ceramic particles is smooth and has no polar groups. If the proportion of carboxyl-terminated liquid rubber-modified epoxy resin in the toughening agent is too large, it will cause uneven distribution in the concrete, and the toughening effect will decrease instead of increase. If the proportion of inorganic ceramic particles in the toughening agent is too large, its smooth surface will affect the aggregation and nucleation of crystalline particles and reduce the crystallization efficiency. Therefore, the ratio of carboxyl-terminated liquid rubber-modified epoxy resin and inorganic ceramic particles in the toughening agent needs to be adjusted and balanced to ensure that the penetrating crystallization waterproofing agent has the best effect on the toughness and impermeability of concrete.

[0012] The inorganic ceramic particles have an average particle size of 10nm-100nm and are selected from one or a combination of two or more of barium titanate, barium strontium titanate, strontium titanate, lead titanate, barium zirconate titanate, lead magnesium niobate, calcium copper titanate, aluminum oxide, magnesium oxide, zirconium oxide, titanium dioxide, silicon nitride, silicon carbide, boron nitride, and zinc oxide.

[0013] The alkylphenol polyoxyethylene ether is selected from one or a combination of two or more of secondary octylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether and dodecylphenol polyoxyethylene ether.

[0014] The non-cement-based cementitious material is selected from one or a combination of two or more of ultrafine mineral powder, fly ash, and silica fume, preferably a mixture of ultrafine mineral powder and fly ash in a mass ratio of 1-3:1.

[0015] Furthermore, the specific surface area of ​​the ultrafine mineral powder is 700-1400m 2 / kg, particles with an average particle size of 1-10μm account for 59-61%, and particles below 1μm account for 26-27%; the 45μm square hole sieve residue of the fly ash is 13-18%; the specific surface area of ​​the silica ash is 500-1000m 2 / kg.

[0016] The thickener is selected from one or a combination of two or more of sodium polyacrylate, polyacrylamide, polyvinyl alcohol, hydroxyethyl cellulose, and carboxymethyl cellulose.

[0017] The water reducer is selected from one or a combination of two or more of polycarboxylic acid water reducers and naphthalene water reducers, and the water reduction rate of the water reducer is 15-25%.

[0018] The alkali activator is not particularly limited and can be selected from one or a combination of two or more of slaked lime, sodium silicate, and sodium sulfate.

[0019] The present invention also provides a method for preparing the above-mentioned penetrating crystalline waterproofing agent, comprising the following steps:

[0020] Add non-cement-based cementitious materials, alkali activator, thickener, toughening agent, dispersant and water reducing agent to a grinder and grind to a fineness of ≥200 mesh to obtain a penetrating crystalline waterproofing agent.

[0021] The present invention also provides a waterproof concrete, comprising the above-mentioned penetrating crystalline waterproofing agent.

[0022] Preferably, the penetrating crystalline waterproofing agent accounts for 3-5wt% of the waterproof concrete cementitious material.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention adopts a toughening agent formed by mixing carboxyl-terminated liquid rubber modified epoxy resin and inorganic ceramic particles in a mass ratio of 7:3-5. Under the action of dispersant alkylphenol polyoxyethylene ether, the toughening agent can be uniformly dispersed in concrete, thereby improving the overall toughness of the concrete. The improvement of the overall toughness can not only withstand the deformation or shrinkage cracking caused by water evaporation, temperature difference, and external stress of the concrete, but also better resist cracking at the source, reduce cracks and pores, prevent water from penetrating, and improve the anti-seepage performance of the concrete; it can also improve the bending resistance of the concrete after it is fully permeable and self-healed. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0026] Cement was purchased from Jidong Cement P·O42.5 silicate cement.

[0027] Sand was purchased from Zhongsha New Materials (Zhaoqing City) Co., Ltd.: medium sand, fineness modulus 2.7.

[0028] The crushed stone was purchased from Shandong Baotian Stone Industry Co., Ltd.: using a continuous gradation of 5-25mm.

[0029] The carboxyl-terminated liquid rubber-modified epoxy resin was purchased from CVC Thermoset Specialties Company, with the brand name HyPox RK84 and epoxy equivalent weight of 1200 g / eq; and the brand name HyPox RK84L and epoxy equivalent weight of 1500 g / eq.

[0030] Zirconia was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd. with a brand name of XT-0806-9-1 and an average particle size of 50 nm.

[0031] The ultrafine mineral powder was purchased from Linxi County Yulan Ultrafine Mineral Powder Co., Ltd., with a specific surface area of ​​1000m 2 / kg, particles with an average particle size of 1-10μm account for 60%, and particles below 1μm account for 27%.

[0032] Fly ash was purchased from Dalian Thermal Power Co., Ltd., and the residue on a 45 μm square sieve was 15%.

[0033] Sodium polyacrylate with a weight average molecular weight of 10 million was purchased from Jinan Huadi Industry and Trade Co., Ltd.

[0034] Nonylphenol polyoxyethylene ether, NP-10, was purchased from Jinan Chenwang Chemical Technology Co., Ltd.

[0035] SSF-1000 series naphthalene-based high-efficiency water-reducing agent has a water-reducing rate of 21.8% and was purchased from Hubei Shanshufeng Building Materials Technology Co., Ltd.

[0036] Preparing waterproof concrete

[0037] Example 1

[0038] 100 parts of non-cement-based cementitious materials prepared by mixing ultrafine mineral powder and fly ash in a mass ratio of 1:1, 25 parts of sodium silicate, 2.5 parts of sodium polyacrylate, 22.5 parts of a toughening agent prepared by mixing end-carboxyl liquid rubber-modified epoxy resin HyPox RK84 and zirconium oxide XT-0806-9-1 in a mass ratio of 7:5, 0.3 parts of nonylphenol polyoxyethylene ether NP-10, and 10 parts of SSF-1000 series naphthalene-based high-efficiency water reducing agent were added to a grinder and ground to a fineness of 250 meshes to obtain a penetrating crystalline waterproofing agent.

[0039] Take 100 parts of cement, 2.11 parts of medium sand, 3.17 parts of crushed stone, add 0.45 parts of water and 5 parts of the above-mentioned penetrating crystalline waterproofing agent, mix evenly, and cure to obtain waterproof concrete.

[0040] Example 2

[0041] The rest is the same as Example 1, except that the mass ratio of the carboxyl-terminated liquid rubber-modified epoxy resin HyPox RK84 and zirconium oxide XT-0806-9-1 in the toughening agent is 7:3.

[0042] Example 3

[0043] The rest is the same as Example 1, except that the amount of toughening agent is 12.5 parts.

[0044] Example 4

[0045] The rest is the same as Example 1, except that HyPox RK84 is replaced by an equal mass of HyPox RK84L.

[0046] Example 5

[0047] The rest is the same as Example 1, except that the nonylphenol polyoxyethylene ether NP-10 is replaced by an equal mass of dodecylphenol polyoxyethylene ether OP-10.

[0048] Example 6

[0049] The rest is the same as Example 1, except that the amount of penetrating crystalline waterproofing agent used is 3 parts.

[0050] Example 7

[0051] 80 parts of non-cement-based cementitious materials prepared by mixing ultrafine mineral powder and fly ash in a mass ratio of 3:1, 15 parts of sodium silicate, 1.5 parts of sodium polyacrylate, 12.5 parts of a toughening agent prepared by mixing end-carboxyl liquid rubber-modified epoxy resin HyPox RK84 and zirconium oxide XT-0806-9-1 in a mass ratio of 7:3, 0.1 part of nonylphenol polyoxyethylene ether NP-10, and 5 parts of SSF-1000 series naphthalene-based high-efficiency water reducing agent were added to a grinder and ground to a fineness of 250 meshes to obtain a penetrating crystalline waterproofing agent.

[0052] Take 100 parts of cement, 2.11 parts of medium sand, 3.17 parts of crushed stone, add 0.45 parts of water and 5 parts of the above-mentioned penetrating crystalline waterproofing agent, mix evenly, and cure to obtain waterproof concrete.

[0053] Comparative Example 1

[0054] The rest is the same as Example 1, except that the mass ratio of the carboxyl-terminated liquid rubber-modified epoxy resin HyPox RK84 and zirconium oxide XT-0806-9-1 in the toughening agent is 7:1.

[0055] Comparative Example 2

[0056] The rest is the same as Example 1, except that the mass ratio of the carboxyl-terminated liquid rubber-modified epoxy resin HyPox RK84 and the zirconium oxide XT-0806-9-1 in the toughening agent is 7:7.

[0057] Comparative Example 3

[0058] The rest is the same as Example 1, except that the nonylphenol polyoxyethylene ether NP-10 is replaced by an equal mass of fatty alcohol polyoxyethylene ether AEO-3.

[0059] The concrete prepared in the above examples and comparative examples was subjected to the following performance tests:

[0060] Anti-seepage performance: Tested with reference to standard GB / T 18445-2012 cement-based penetrating crystalline waterproof materials.

[0061] Flexural strength: The test is carried out in accordance with the standard GB / T 50081-2019 Test method for physical and mechanical properties of concrete, and the flexural strength of the concrete is tested after 28 days of curing, and the flexural strength before the second anti-seepage test (56 days) in the above anti-seepage performance test.

[0062] Table 1

[0063]

[0064] It can be seen from Table 1 that the toughening agent composed of a mixture of a carboxyl-terminated liquid rubber-modified epoxy resin and inorganic ceramic particles in a mass ratio of 7:3-5 has the effect of significantly improving the flexural properties of concrete and concrete after water permeation and healing.

[0065] It can be seen from the anti-seepage performance test results that the penetrating crystalline waterproofing agent has excellent anti-seepage performance.

[0066] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A penetrating crystalline waterproofing agent, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of non-cement-based cementitious materials, 15-25 parts of alkali activator, 1.5-2.5 parts of thickener, 12.5-22.5 parts of toughening agent, 0.1-0.3 parts of dispersant and 5-10 parts of water reducing agent. The toughening agent is prepared by mixing carboxyl-terminated liquid rubber-modified epoxy resin and inorganic ceramic particles in a mass ratio of 7:3-5. The dispersant is alkylphenol polyoxyethylene ether.

2. The penetrating crystalline waterproofing agent according to claim 1, characterized in that: The carboxyl-terminated liquid rubber modified epoxy resin is an adduct of carboxyl-terminated liquid rubber and epoxy resin, and has an epoxy equivalent of 1200-1800 g / eq.

3. The penetrating crystalline waterproofing agent according to claim 1, characterized in that: The inorganic ceramic particles have an average particle size of 10nm-100nm and are selected from one or a combination of two or more of barium titanate, barium strontium titanate, strontium titanate, lead titanate, barium zirconate titanate, lead magnesium niobate, calcium copper titanate, aluminum oxide, magnesium oxide, zirconium oxide, titanium dioxide, silicon nitride, silicon carbide, boron nitride, and zinc oxide.

4. The penetrating crystalline waterproofing agent according to claim 1, characterized in that: The alkylphenol polyoxyethylene ether is selected from one or a combination of two or more of secondary octylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether and dodecylphenol polyoxyethylene ether.

5. The penetrating crystalline waterproofing agent according to claim 1, characterized in that: The non-cement-based cementitious material is selected from one or a combination of two or more of ultrafine mineral powder, fly ash, and silica fume; preferably, it is a mixture of ultrafine mineral powder and fly ash in a mass ratio of 1-3:

1.

6. The penetrating crystalline waterproofing agent according to claim 5, characterized in that: The specific surface area of ​​the ultrafine mineral powder is 700-1400m 2 / kg, particles with an average particle size of 1-10μm account for 59-61%, and particles below 1μm account for 26-27%; the 45μm square hole sieve residue of the fly ash is 13-18%; the specific surface area of ​​the silica ash is 500-1000m 2 / kg.

7. The penetrating crystalline waterproofing agent according to claim 1, characterized in that: The thickener is selected from one or a combination of two or more of sodium polyacrylate, polyacrylamide, polyvinyl alcohol, hydroxyethyl cellulose, carboxymethyl cellulose; the water reducer is selected from one or a combination of two or more of polycarboxylic acid water reducer and naphthalene water reducer, and the water reduction rate of the water reducer is 15-25%; the alkali activator is selected from one or a combination of two or more of slaked lime, sodium silicate and sodium sulfate.

8. The method for preparing the penetrating crystalline waterproofing agent according to any one of claims 1 to 7, characterized in that: The steps include: Add non-cement-based cementitious materials, alkali activator, thickener, toughening agent, dispersant and water reducer to a grinder and grind to a fineness of ≥200 mesh to obtain a penetrating crystalline waterproofing agent.

9. A waterproof concrete comprising the penetrating crystalline waterproofing agent according to any one of claims 1 to 7 or 8.

10. The waterproof concrete according to claim 9, characterized in that: The penetrating crystalline waterproofing agent accounts for 3-5wt% of the waterproof concrete cementitious material.

Citation Information

Patent Citations

  • Inorganic cement capillary crystalline waterproofing agent and production process thereof

    CN102060460B

  • Permeable crystallization waterproof agent

    CN102432222B

Cited By

  • C80-grade concrete with improved low-temperature toughness and preparation method thereof

    CN119797856A

  • A kind of concrete with C80 grade for improving low-temperature toughness and its preparation method

    CN119797856B